Women’s Movement for Gender Quotas in Nigeria and Ghana - Ronke I. Ako-Nai; Babatunde F. Obamamoye (Modern Africa, 2018)
The third wave of the international women’s movement expressly broadened the focus of women’s activism to incorporate the clamour for more political representation of women. Within the confines of the struggle, women in Nigeria and Ghana have initiated a movement for gender quotas that will improve their inclusion in decision-making processes. However, there is a paucity of scholarly work on the patterns and precipitating factors of the movement in the context of both states. Against this background, this article draws on interview data to examine the comparative dynamics of the women’s movement for gender quotas in Nigeria and Ghana. It specifically offers explanations of why and how women channel their struggle for political emancipation in both states.